2012
DOI: 10.1186/1757-1146-5-19
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the ankle brachial index amongst podiatrists registered in Western Australia

Abstract: Background: The ankle brachial index (ABI) is an objective diagnostic tool that is widely used for the diagnosis of peripheral arterial disease. Despite its usefulness, it is evident within the literature that many practitioners forgo using this screening tool due to limiting factors such as time. There is also no recommended technique for ABI measurement. The purpose of this study is to investigate the perceptions of the use of ABI clinically among Western Australian podiatrists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
2
11
1
Order By: Relevance
“…Performing a comprehensive examination of the foot, including neurovascular and musculoskeletal assessments, is core general podiatry practice recommended by the Australian and New Zealand Podiatry Accreditation Council [ 28 ], thus, a high adherence rate to the diabetes guidelines for these items that relate is understandable. Performing an ABI or toe pressure was the only item to score below “very often” and aligned with a similar finding in a recent study of Western Australian podiatrists that reported 63% of podiatrists use the ABI [ 29 ]. These findings may also be expected as guideline recommendations typically suggest using an ABI or other non-invasive vascular assessment when pedal pulses are not readily palpable [ 4 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Performing a comprehensive examination of the foot, including neurovascular and musculoskeletal assessments, is core general podiatry practice recommended by the Australian and New Zealand Podiatry Accreditation Council [ 28 ], thus, a high adherence rate to the diabetes guidelines for these items that relate is understandable. Performing an ABI or toe pressure was the only item to score below “very often” and aligned with a similar finding in a recent study of Western Australian podiatrists that reported 63% of podiatrists use the ABI [ 29 ]. These findings may also be expected as guideline recommendations typically suggest using an ABI or other non-invasive vascular assessment when pedal pulses are not readily palpable [ 4 ].…”
Section: Discussionsupporting
confidence: 83%
“…For all items reporting a low adherence rate, public-employed podiatrists reported higher adherence rates than private-employed podiatrists and also had greater access to multidisciplinary teams. Chen et al also found that rates of ABI use were also higher in public sector than private podiatry [ 29 ]. There are a variety of hypotheses why this may be the case including that public podiatrists see a larger volume of patients with diabetic foot ulcers in particular, and thus, more inclined to be aware of and use best practice management recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…As the toe-brachial index (TBI) measurement is taken more distally in the lower limb there is a greater likelihood of detecting arterial pressure changes caused by stenosis located below the knee as occur in the presence of diabetes [9]. The digital arteries are also less likely to be affected by MAC [10][11][12], and these factors potentially make the TBI a more sensitive test for A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…Hand-held Doppler ultrasound examination (Doppler) of pedal arteries is the most frequently used non-invasive vascular assessment modality utilised by podiatrists [ 8 ] for diagnosis and ongoing monitoring of PAD. Podiatrists generally use Doppler in two different ways, as part of an ankle brachial index (ABI) or as a standalone test [ 8 ].…”
Section: Introductionmentioning
confidence: 99%